Nghiên cứu hành vi tuân thủ thuế thu nhập cá nhân của người nộp thuế tại TP. Hồ Chí Minh - Dương Thị Bình, Minh; Vũ Thị Bích, Quỳnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
Voluntary tax compliance is a salient issue of modern tax administration, as well as a major concern of both developed and developing countries around the world. The study aims at examining the influence of social factors on individuals’ tax compliance intentions. The survey of 274 taxpayers in Ho Chi Minh City reveals the relationship amongs examined variables. The results indicate that social norms indirectly impact on personal income tax compliance through personal norms which also play an intermediary role in the influence of perceived grand corruption, perceived petty corruption, and perceived tax fairness on tax compliance. The paper attempts to solve limitations of the previous studies on personal income tax administration in both theoretical aspect and methodology; thereby suggesting and examining research models and hypotheses on tax compliance in the context of global economic integration in Vietnam, and then making recommendations about implications, limitations, as well as further research.
Keywords: Tax compliance; Personal income tax; Social norms; Personal norms; Perceived grand corruption; Perceived petty corruption; Perceived tax fairness